2020
DOI: 10.1155/2020/2170606
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Values of Transforming Growth Factor-Beta Subtypes in Ovarian Cancer

Abstract: Purpose. To explore the potential role of the transforming growth factor-beta (TGF-β) subtypes in the prognosis of ovarian cancer patients. Materials and Methods. The prognostic roles of individual TGF-β subtypes in women with ovarian cancer were retrieved from the Kaplan-Meier plotter (KM plotter) database. In addition, the Oncomine database and immunohistochemistry were used to observe the mRNA and protein expression of TGF-β subtypes between human ovarian carcinoma and normal ovarian samples, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“… 62 The Tregs then produce more TGF-β, further increasing immunosuppression within the tumor, which impedes CAR T-cell function. High levels of TGF-β within the TME have been shown to correspond to poor prognosis in patients, 63–65 demonstrating that reducing TGF-β mediated immunosuppression in solid tumors may be key to enhancing CAR T-cell efficacy and clinical outcome.…”
Section: Armored Car T-cellsmentioning
confidence: 99%
“… 62 The Tregs then produce more TGF-β, further increasing immunosuppression within the tumor, which impedes CAR T-cell function. High levels of TGF-β within the TME have been shown to correspond to poor prognosis in patients, 63–65 demonstrating that reducing TGF-β mediated immunosuppression in solid tumors may be key to enhancing CAR T-cell efficacy and clinical outcome.…”
Section: Armored Car T-cellsmentioning
confidence: 99%
“…Such studies have revealed lack of a robust correlation between TGFβ1 expression and survival outcomes in women with ovarian cancer. However most notably, increased TGFβ2 and TGFβ3 mRNA expression were associated with poorer prognosis based on worse progression-free survival (PFS) and reduced overall survival (OS) [ 145 ]. While the utility of the TGFβ ligand expression as a biomarker continues to be debated, there is significant evidence that all isoforms are produced albeit at different locations and to different degrees.…”
Section: Tgfβ Family In Ovarian and Related Cancersmentioning
confidence: 99%
“…transformation of fibroblasts and regulate cell proliferation and apoptosis (56). The high expression of TGF-β3 is associated with poor prognosis of high-grade serous carcinoma, and it is a potential indicator for the evaluation of ovarian cancer prognosis (57). Recent studies have reported that in ovarian cancer stem cells, inhibition of TGF-β/SMAD pathway activation can further inhibit EMT (58)(59)(60).…”
Section: Cell Signaling and Exosome-mediated Tumor Immune Microenviromentioning
confidence: 99%